1996
DOI: 10.1007/bf00032445
|View full text |Cite
|
Sign up to set email alerts
|

Coat protein-mediated protection to cucumber mosaic virus infections in cultivated tomato

Abstract: Cucumber mosaic virus (CMV) infections rank among the most devastating diseases in the commercial culture of tomato (Lycopersicon esculentum Mill .), for which suitable sources of natural resistance are not available . The concept of pathogen-derived resistance, however, offers an alternate approach to combat plant viral diseases by transformation of crops with nucleotide sequences derived from the viral genome . This report demonstrates the successful application of such a pathogen-derived resistance gene com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 34 publications
(28 reference statements)
2
6
0
Order By: Relevance
“…Evaluation of resistance in different plant lines to CMV infection in the T1 generation as determined by virus accumulation levels at different times (dpi) and from different locations of leaf (inoculated leaf and/or upper leaf) indicated that it ranged from near-complete resistance to none. Primarily, all resistant transgenic plants (>50%) exhibited delayed symptom development as reported in a number of studies (Nakajima et al 1993;Gielen et al 1996) though a few strongly resistant plants were also obtained where no symptoms developed even as late as 30 dpi.…”
Section: Discussionsupporting
confidence: 63%
“…Evaluation of resistance in different plant lines to CMV infection in the T1 generation as determined by virus accumulation levels at different times (dpi) and from different locations of leaf (inoculated leaf and/or upper leaf) indicated that it ranged from near-complete resistance to none. Primarily, all resistant transgenic plants (>50%) exhibited delayed symptom development as reported in a number of studies (Nakajima et al 1993;Gielen et al 1996) though a few strongly resistant plants were also obtained where no symptoms developed even as late as 30 dpi.…”
Section: Discussionsupporting
confidence: 63%
“…Susceptible transgenic plants initially showed chlorosis in the inoculated leaves in one week but appearance of systemic mosaic symptoms in them was observed only after 10-15 dpi. These findings are in accordance with those reported by Nelson et al (1987);Tumer et al (1987a); Nakajima et al (1993); Gielen et al (1996) who showed delaying in the systemic spread of the infecting virus in the transgenic plants (tobacco or tomato) expressing the viral CP. At the same time five plants from each A, D, E, H lines challenged from CMV isolates through mechanical inoculation were showed delay in symptoms appearance and resistant to CMV (Table 2).…”
Section: Discussionsupporting
confidence: 82%
“…Successful production of the crop in the tropics, however, suffers from environmental variations, especially in the open fields. This affects growth of the crop leading to poor yield and quality [3][4][5].…”
Section: Introductionmentioning
confidence: 99%